Modeling of indoor thermal comfort in the intelligent building. Issue 1 (1st September 2022) - Krawczyk, N; Dębska, L
Abstract: Thermal comfort is generally determined with the Fanger model, which originates from the 60's. Its accuracy can be considered disputable and it is often challenged, however it is the basis for the international standards up to this day - namely ISO 7730 and ASHRAE-55 (US standard). The present work aims to develop a modified correlation based on experimental measurements made with questionnaires and the Testo 400 microclimate meter. The original model is modified in such a way that the concentration of carbon dioxide is taken into account (the original model does not take it into account at all). The experimental results have proven to be in good agreement with the modified correlation in the wide range of CO2 levels. The modification that included CO2 provided more accurate results than the original model, proving that the concept is justified.